Cultural Ecosystem Services of Geodiversity: A Case Study from Stránská skála (Brno, Czech Republic) - Lucie Kubalíková (Land, 2020)
The concept of ecosystem services developed in the second half of the 20th century, and the Millennium Ecosystem Assessment was crucial for its acceptance. This assessment identified the services that ecosystems provide to society, but geodiversity (as an indispensable component of ecosystems) was somewhat underestimated. At present, geodiversity is intensively used by human society and it provides numerous services including cultural as a resource for tourism, recreation, as a part of natural heritage, and to satisfy matters of spiritual importance. The main purpose of this paper is to present the geocultural issues of Stránská skála (a limestone cliff with caves and an anthropogenic underground) in Brno (Czech Republic) and to evaluate the cultural ecosystem services of geodiversity by using the abiotic ecosystem services approach. This assessment of cultural ecosystem services of the Stránská skála enables the identification and description of the functions and services which are provided by geodiversity and confirms the high cultural and geoheritage value of the site.